FORMULASI SEDIAAN SHAMPO EKSTRAK ETANOL DAUN KOPI ARABIKA (Coffea arabica L.) DAN EVALUASI FISIKNYA - Yahdian Rasyadi; Diana Agustin; Octaviana Gunawan (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
A hair problem that can interfere with the appearance and beauty of hair is dandruff. One way to treat dandruff is to use anti-dandruff shampoo. Arabica coffee leaves (Coffea arabica L.) contain various chemical compounds so they have the potential to be used as active substances in shampoo preparations. The aim of this research is to develop a shampoo preparation formula for ethanol extract of Arabica coffee leaves and look at its physical evaluation. Each shampoo contains 0% (F0), 15% (F1), 20% (F2), 30% (F3), 45% (F4), 60% (F5) ethanol extract of Arabica coffee leaves and a physical evaluation is carried out. including organoleptic tests, homogeneity tests, pH tests, foam height tests, stability tests, pH tests, stability tests and viscosity tests. The organoleptic test results showed that F0 was colorless, F1-F5 were blackish green, all formulas were in the form of a thick mass and had the aroma of coffee. The examination results showed that all formulas were homogeneous; pH ranges from 5.0 to 9.0; foam height ranges from 1.62 to 3.97 cm; the preparation does not separate (stable); viscosity ranges from 1247-3011 cp. From various physical evaluation results, it can be concluded that Arabica coffee leaf ethanol extract shampoo can be made into a shampoo that meets the requirements.